2001
DOI: 10.1038/sj.gt.3301536
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible transgene expression in differentiated human NT2N neurons – a cell culture model for gene therapy of postischemic neuronal loss

Abstract: Expression of anti-apoptotic or neurotrophic transgene proteins in hypoxic neurons may provide a novel therapeutic strategy for neuroprotection and alleviation of damage to ischemic brain areas. NT2, a human neoplastic cell line which terminally differentiates into postmitotic neuronsIschemia of the brain due to major vessel thrombosis causes hypoxia in the respective vascular territory and subsequently induces neuronal death which is at least in part caused by apoptosis, especially in the penumbra of the lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Previous studies demonstrated efficient VEGF promotermediated induction of transgene expression in hypoxic human neurons in culture. 6 The present study employed two different types of bcl-2 expression cassettes in two different plasmid vectors: one driven by the strong constitutive cytomegalovirus promoter (pCMV) and another based on the hypoxia-inducible VEGF promoter (pHRE). 6 The expression plasmids pCMV-bcl2 and pHRE-bcl2 could be efficiently transfected into rat brain in vivo.…”
Section: Injection Using a 100 L Hamilton Microsyringe (Hamilton Renmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies demonstrated efficient VEGF promotermediated induction of transgene expression in hypoxic human neurons in culture. 6 The present study employed two different types of bcl-2 expression cassettes in two different plasmid vectors: one driven by the strong constitutive cytomegalovirus promoter (pCMV) and another based on the hypoxia-inducible VEGF promoter (pHRE). 6 The expression plasmids pCMV-bcl2 and pHRE-bcl2 could be efficiently transfected into rat brain in vivo.…”
Section: Injection Using a 100 L Hamilton Microsyringe (Hamilton Renmentioning
confidence: 99%
“…6 The present study employed two different types of bcl-2 expression cassettes in two different plasmid vectors: one driven by the strong constitutive cytomegalovirus promoter (pCMV) and another based on the hypoxia-inducible VEGF promoter (pHRE). 6 The expression plasmids pCMV-bcl2 and pHRE-bcl2 could be efficiently transfected into rat brain in vivo. Lipoplexes were injected intrathecally immediately after occlusion of the middle cerebral artery (MCA).…”
Section: Injection Using a 100 L Hamilton Microsyringe (Hamilton Renmentioning
confidence: 99%
See 3 more Smart Citations